2020
DOI: 10.1155/2020/3920735
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Evaluation of Traditional Chinese Medicine (Qingre‐Lishi‐Yishen Formula) Based on Treatment of Regular Glucocorticoid Combined with Cyclophosphamide Pulse in Children Suffered from Moderately Severe Henoch–Schonlein Purpura Nephritis with Nephrotic Proteinuria

Abstract: Objective. At present, the most appropriate management of Henoch–Schonlein purpura nephritis (HSPN) with nephrotic-range proteinuria still remains controversial; thus, the purpose of this study is to evaluate safety and efficacy of traditional Chinese medicine (TCM), Qingre-Lishi-Yishen Formula (QLYF), integrated with regular oral glucocorticoid and cyclophosphamide intravenous pulse therapeutic regimen in children suffered from moderately severe HSPN with nephrotic proteinuria. Methods. From 1 January 2012, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At present, more attention has been focused on Traditional Chinese Medicine (TCM) with its well-defined and established therapeutic system. [ 23 ] TCM, with traditional Chinese syndrome differentiation as the core, has a stable effect in the treatment of IBS-D. Tong-Xie-An-Chang Decoction (TXACD), created by professor Jun-xiang Li from Dongfang Hospital, Beijing University of Chinese Medicine, has been shown to be effective in relieving abdominal pain in IBS-D patients in our previous randomized positive controlled clinical trial. [ 15 ] Simultaneously, in IBS-D experimental rat model, TXACD was proved that it could reduce the fecal water content and abdominal withdrawal reflex (AWR) score, used to evaluate visceral sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…At present, more attention has been focused on Traditional Chinese Medicine (TCM) with its well-defined and established therapeutic system. [ 23 ] TCM, with traditional Chinese syndrome differentiation as the core, has a stable effect in the treatment of IBS-D. Tong-Xie-An-Chang Decoction (TXACD), created by professor Jun-xiang Li from Dongfang Hospital, Beijing University of Chinese Medicine, has been shown to be effective in relieving abdominal pain in IBS-D patients in our previous randomized positive controlled clinical trial. [ 15 ] Simultaneously, in IBS-D experimental rat model, TXACD was proved that it could reduce the fecal water content and abdominal withdrawal reflex (AWR) score, used to evaluate visceral sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Henoch-Schönlein purpura nephritis is a common disease in children[ 8 - 10 ]. Clinical studies have shown that the disease is an allergic reaction caused by bacteria, such as Legionella or Salmonella, viruses such as rubella virus or varicella virus, parasites such as roundworm and Mycoplasma, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Despite conventional medications to control HSP, such as anti-inflammatory drugs, corticosteroids, cytotoxic drugs and immunosuppressants ( 8 , 127 , 128 ). These measures are unsuitable for long-term use due to the high cost, transient efficacy and severe adverse effects, like long-term and large-scale use of glucocorticoids could cause infections and Cushing's syndrome; long-term use of cytotoxic drugs that could result in gastrointestinal reactions, hepatotoxicity, bone marrow suppression, reproductive toxicity, cardiotoxicity ( 12 ). Proanthocyanidins, as natural extracts from plants, have widespread sources and diverse bioactivity with minimal side effects and can be used by pregnant people ( 118 ).…”
Section: Clinical Significancementioning
confidence: 99%
“…However, these therapies exhibit poor efficacy and do not stop recurrence, research has shown that relapses occur in about 25% of patients and that children over age 8 or those with kidney-based disease are more prone to relapse ( 11 ); furthermore, most approaches to HSP are unsuitable for long-term application owing to high expenditures and adverse side effects, e.g. long-term and large-scale use of glucocorticoids could cause infections and Cushing's syndrome; long-term use of cytotoxic drugs that could result in gastrointestinal reactions, hepatotoxicity, bone marrow suppression, reproductive toxicity, cardiotoxicity ( 12 ). Thus, a novel and effective cure for HSP is required.…”
Section: Introductionmentioning
confidence: 99%